An Unusual Case of Solitary Osteochondroma of the Iliac Wing. (18th December 2020) - Thomas, Christopher; Sanderson, Brent; Horvath, Dennis G.; Mouselli, Michael; Hobbs, Janet
Abstract : Introduction . Osteochondromas represent one of the most common bone tumors accounting for 8% of all bone tumors. While most osteochondromas arise in the metaphysis of long bones, osteochondromas have been reported in atypical locations such as the scapula, metatarsals, and the pelvic region. Osteochondromas are capable of growing large enough to cause mass effects and can undergo malignant transformation, stressing the clinical importance of recognizing these tumors. Case Presentation . In this case, we present an 18-year-old skeletally mature Caucasian male with a symptomatic osteochondroma arising from the iliac wing. The osteochondroma increased in size since he reached skeletal maturity. This resulted in a mass effect that interfered with activities of daily living, including clothing wear and symptomatic impaction on hard surfaces. Conclusion . The majority of osteochondromas arise from the metaphysis of long bones, but case reports have shown that osteochondromas presenting in atypical locations such as the pelvis do occur. In the case of our patient, his asymptomatic pelvic tumor grew to the extent that it was causing interference with activities of daily living. Surgical excision of his tumor proved to be curative, and there was no recurrence at 6 months after excision. Osteochondromas in this region are capable of growing large enough to cause sexual dysfunction. Clinical suspicion must be high to properly diagnose osteochondromas in atypical locations. All providers, particularly those in primary care, should be aware of these locations as patients with symptomatic mass lesions will likely initially present here.